Libyan EFL Teachers’ Perceptions of AI Integration in English Teaching: A Case Study at Benghazi University. - Mahmoud Hadaga, Hana; Mohammed Elfalfal, Amal (Scientific Journal of University of Benghazi, 2025)
There is an inevitability and increasing use of technologies such as Artificial Intelligence (AI) in language teaching and learning. This research investigates EFL Libyan teachers’ perceptions of the effectiveness of integrating AI tools in EFL teaching in the Libyan context. The study employed a quantitative approach of research in which a questionnaire was distributed to collect data from 20 EFL Libyan teachers in the department of applied linguistics at the Faculty of Languages at Benghazi University in Libya. The questionnaire examined data relevant to Libyan EFL teachers’ perspectives on integrating AI in their teaching process and the challenges encountered. The results showed that most participants had a positive attitude towards using AI in their teaching. The majority believed that AI is important for helping students improve their language skills and making English teaching more effective. In addition, they mutually agreed that AI encouraged their students to participate more actively in class and helped to reduce their anxiety about making mistakes. However, the study revealed that participants collectively faced challenges in using AI. One major challenge was that they mostly relied on self-study to learn about these technologies rather than formal training. Findings of this study provide feedback to the head dean of the Department of Applied Linguistics for possible improvements. Furthermore, these findings can inform future enhancement initiatives in other similar Libyan EFL contexts. A better integration of AI into educational settings is needed, and more support and training are necessary for successful implementation.